Professional online group discussion proz.com to enhance students’ accuracy in translating legal document - Lutviana, Rizky; Liskinasih, Ayu; Ardhana, Alwi Atma (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Legal document is a subject matter text which has distinct characteristics and its own system and culture that caused difficulties for translators, especially trainee or semi-professional translator. The most advanced CAT, proZ.com could help the translator to translate legal document with its sophisticated facilities and allowed the translator to search legal terminology quickly and effectively. The purpose of this study was to use professional online group discussion forum, namely proZ.com to improve students’ skill in translating legal document non-disclosure agreement (NDA). This study employed classroom action research (CAR) to 31 students majoring English Education who took translation course as taught by both professional translator and the researcher. The participant was chosen using homogeneous sampling method in which students were selected based on certain characteristics (Creswell, 2012). The instruments used in this study were (1) test to measure students’ achievement in learning, (2) questionnaire to measure students’ attitude toward the implementation of the technique, and (3) in depth interview to gain students’ opinion about the benefit of proZ.com. it is found that proZ.com could improve students’ skill in translating NDA since it helped students to find the most correct translation terms in a target language from its database quickly and practically, since proZ.com offered the translation from the various fields. It is important to teach student to be sensitive in context so that their translation is acceptable.